2005
DOI: 10.54830/bmnhn.v54.2005.286
|View full text |Cite
|
Sign up to set email alerts
|

Presencia del género Paleolama P. Gervais (Artiodactyla, Camelidae) en el extremo meridional del Semiárido de Chile (Los Vilos- IV Región)

Abstract: Las investigaciones arqueológicas y paleontológicas desarrolladas en el norte semiárido de Chile (IV Región) han permitido recuperar en depósitos del Pleistoceno tardío un abundante registro de mamíferos extintos. Dentro de este elenco, se incluye al género Palaeolama Gervais, 1867 (Camelidae), identificado en contextos superficiales y estratigráficos localizados geográficamente en la Comuna de Los Vilos (31° S). El anáhs1s de estos restos fósiles, distribuidos en la franja costera del semiárido, señalan la pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The northern trans-Andean route, in turn, may have been linked to a possible natural dispersal route through the current Chilean territory, following the course of the Loa River whose source is located near the border of Chile with Bolivia at about 4000 m asl. A lumbar vertebra assigned to an undetermined canid of comparable size to the canids studied here (recently observed by Rafael Labarca, see also López et al, 2005), found in Ojos de Opache in the altiplano of northern Chile at 2200 m asl, and about 180 km southeast of Pampa del Tamarugal (López et al, 2005), lend further support to these dispersal routes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The northern trans-Andean route, in turn, may have been linked to a possible natural dispersal route through the current Chilean territory, following the course of the Loa River whose source is located near the border of Chile with Bolivia at about 4000 m asl. A lumbar vertebra assigned to an undetermined canid of comparable size to the canids studied here (recently observed by Rafael Labarca, see also López et al, 2005), found in Ojos de Opache in the altiplano of northern Chile at 2200 m asl, and about 180 km southeast of Pampa del Tamarugal (López et al, 2005), lend further support to these dispersal routes.…”
Section: Discussionsupporting
confidence: 83%
“…are known from the Pampa del Tamarugal (PdT) basin (Casamiquela, 1969(Casamiquela, -1970 and Canidae indet. from the Ojo de Opache (Calama basin) locality (López et al, 2005).…”
Section: Introductionmentioning
confidence: 99%